Life Skills Education for Students with Special Needs to Improve Independence and Skills in Daily Life at UPT SLBN 2 Makassar - Muhammad Jusmirad; Muhammad Fauzan Khibran; Irfawandi; Yuni Sarah; Syamsinar Rusmiati Songkeng; Alya Arina (PT FORMOSA CENDEKIA GLOBAL, 2023)
This service aims to provide life skills education about independence and skills for students with special needs so that they can face everyday life more independently. The method used is skills training, which consists of three stages, namely the preparation, training, and evaluation stages, to assess the effectiveness of the training program and provide feedback for improvement and development of the program in the future. Skills training covers basic skills such as taking care of yourself, managing finances, and communicating with the surrounding environment. The results of the study show that this activity can improve students' ability to face everyday life more independently and increase their role in society. The training also helps students gain self-confidence and improve their quality of life. In addition, this training also received support from parents and the school.